Nothing is difficult in facing the pandemic covid-19: Best practice library services at UIN Sunan Kalijaga Yogyakarta during pandemic - Ismiyatin; Ida Nor'aini Hadna (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2022)
This paper was written to know the readiness of the librarians of UIN Sunan Kalijaga to face the Covid-19 pandemic. The Covid-19 pandemic that has hit almost the world has changed the lifestyle of humankind. Minimizing direct physical contact with other people is an effective preventive measure for spreading the virus. This study uses the Best Practice Method because the activities carried out by librarians so far are the same as those carried out in facing this pandemic. These activities are proven to lead to better change, overcome current problems, provide benefits, can be evaluated, and can provide inspiration for others. To face the development of Information Technology (IT), the UIN Sunan Kalijaga Library has made many innovations, including (1) self-check service; (2) Dealkey service ; (3) digital signage; (4) Final Project independent upload service; (5) online services, and others. The UIN Sunan Kalijaga library has also tried to provide facilities that enable users to perform services independently, using MPS (Multipurpose Station) based on RFID. Through Information Technology, commonly practiced by the UIN Sunan Kalijaga Library, changes in service patterns during the Covid-19 pandemic are not a surprise for librarians at UIN Sunan Kalijaga.